First photographic record of Leopardus pardalis (Mammalia: Felidae) in Nichupté Lagoon, Quintana Roo, Mexico - Cruz-Hernández, Patricia; Hernández-May, Manuel Alberto; Martínez-Sánchez, Aldo J; Villar-Bedian, Carlos Manuel; Nungaray-Núñez, José Antonio; García-Leyva, Juan Francisco; Cárdenas-De la Rosa, Carlos Antonio; Hernández-Maruri, Héctor (Therya Notes, 2026)
The ocelot (Leopardus pardalis) is one of six species of felines found in Mexico. According to NOM-059-SEMARNAT-2010, it is currently endangered in the country. The objective of this study was to document the presence of ocelots in the Nichupté mangrove protected natural area in Quintana Roo, Mexico. From March to November 2024, 16 camera traps were used for faunal sampling in this ecosystem for 275 days and 6,600 hours. From May to July 2025, daytime surveys were conducted for 65 days and 455 hours. Independent photographs and videos of several species of fauna were obtained. However, the ocelot was observed in only one photograph and in a single footprint on one day. This is the first documented instance of ocelots in the Nichupté mangrove ecosystem, which is of high biological and ecological importance. Furthermore, the presence of this species suggests that the ecosystem is healthy, as the ocelot is mainly associated with its food sources, such as rodents and birds.